Adopting information and communications technology in the control, prevention, and management of stroke: perspectives from patients and providers in Uganda - Namyalo, Prossy Kiddu; Setekera, Robert; Nakazibwe, Primrose (Frontiers in Stroke, 2024)
ObjectiveThe stroke burden in Uganda ranks ninth among the ten causes of death, a major cause of chronic illnesses, accounting for the top ten causes of hospitalization. This baseline study examined how mobile phones can improve the prevention, management, and treatment of stroke in rural Uganda.MethodsIt was a cross-sectional study that utilized a mixture of methods. Quantitative data was collected from the districts' health information management system while qualitative data were from healthcare providers and patients/caregivers/survivors using a semi-structured guide. Quantitative data was analyzed descriptively while qualitative data was inductively analyzed through creating themes.ResultsAll participants supported the use of mobile phone interventions and suggested three major types of information to be included in this intervention: warning signs and indicators, underlying causes of stroke, and prevention measures. The challenges that might be faced in implementing this intervention are contextual, health system, and economic related.ConclusionThese baseline findings support the possibility of mobile phone intervention as an important instrument to improve stroke prevention, management, and treatment in rural Uganda. Challenges that might accompany the use of ICT have to be addressed as the intervention is designed.